X−SOM Results for OAEI 2007 - Curino, C; Orsi, G; Tanca, L (2007)
This paper summarizes the results of the X-SOM tool in the OAEI 2007 campaign. X-SOM is an extensible ontology mapper that combines various matching algorithms by means of a feed-forward neural network. X-SOM exploits logical reasoning and local heuristics to improve the quality of mappings while guaranteeing their consistency.